La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Nouveaux cahiers de recherche, 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Les îles (2011) d’Isabelle Panneton et l’héritage de Philippe Boesmans : généalogie d’une démarche compositionnelle - Brasset, Marie-Pierre (Circuit : musiques contemporaines, 2021)
Dans les années 1980, après ses études auprès de Gilles Tremblay, Isabelle Panneton fait la rencontre de Philippe Boesmans lors d’un passage du compositeur belge à Montréal. Impressionnée par sa musique, elle se rendra en Belgique pour y suivre des leçons de composition avec lui de 1984 à 1987. Cette période sera déterminante pour la compositrice, ouvrant toute grande la porte à l’émergence de sa personnalité musicale. Ce texte retrace les moments forts du passage d’Isabelle Panneton chez le compositeur belge et met en lumière les liens qui les unissent, en guise de prélude à l’analyse de son trio Les îles pour violon, violoncelle et piano.
Keywords: Belgique; Belgium; Isabelle Panneton; Philippe Boesmans; chamber music; développement motivique; motivic development; musique de chambre

Chronologie de plus de cent ans de présence féminine dans la création d'œuvres musicales au Québec : un premier survol - Lefebvre, Marie-Thérèse (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Avant-propos. Björk, Montréal et le Nunavut - McKinley, Maxime (Circuit : musiques contemporaines, 2021)
An article from Circuit, on Érudit.

TAGS de Joane Hétu et TanGRAM de Danielle Palardy Roger : signatures plurielles et figure continue - Dall’Ara-Majek, Ana (Circuit : musiques contemporaines, 2020)
TAGS by Joane Hétu and TanGRAM by Danielle Palardy Roger are two written works that showcase graphic scores in improvised music. TAGS creates an encounter between Ensemble SuperMusique, the saxophone quartet Quasar, and the Bozzini Quartet. The musicians make “sound graffiti” on an imaginary wall represented by a sequence of timed sections on a descriptive score where the composer uses different instrumental combinations. Using an aesthetic of articulated gestures, the work is made through these multiple signatures. TanGRAM brings together twenty instrumentalists from Ensemble SuperMusique. The game of Tangram is represented in the form of a graphic score where each piece has specific musical properties to be interpreted by the musicians. Rich in combinatorial and symmetrical games, the work presents Orion: a continuous figure, a slowly moving flow where each musician seeks their own way in a global sound.
Keywords: Analyse musicale; Danielle Palardy Roger; Joane Hétu; Musical analysis; graphic score; improvised music; musique improvisée; partition graphique

Jocelyne Binet's Cycle de Mélodies: Unearthing a Forgotten Song Cycle - Hoch, Matthew (Journal of Singing, 2020)
Montreal composer Jocelyne Binet's "Cycle de Melodies sur des Poemes de Paul Eluard" was programmed in 1955 by the French baritone Gerard Souzay in a performance that was most likely the world premiere. Unfortunately, Binet's song cycle never was published, and the work soon was forgotten. In the fall of 2016, the author discovered Bineet's original handwritten manuscript pages in holdings of Bibliotheque et Archives Nationales du Quebec and began the process of reconstructing the score. This article discusses the editorial journal undertaken when resurrecting Binet's forgotten song cycle, which was subsequently published in 2018 by Classical Vocal Reprints.
Keywords: Archives & records; Education; French language; Manuscripts; Music; Musical performances; Online data bases; Piano; Spelling; Vocal music

Ageing with Waves: The Im/material Worlds of Two Quebec Ondists - Madden, David (A Senior Moment: Cultural Mediations of Memory and Ageing, 2020)
Ageing and memory - two aspects of life everybody has to face eventually. The contributions to this volume explore the cultural mediations of these categories. Through a series of approaches focused on practices and acts of memory, narratives, reminiscence, representation and collective memory, they seek to better understand and critically reflect on how ageing is experienced in variegated ways across the lifespan. By covering a variety of phenomena, from biopics, music by the elderly, and artefacts, among other, they all contribute to further the understanding of memory as a cultural process always in the making - situated in particular contexts, and shaped by its material conditions of existence.

Tuning a Room: Designs for Hearing According to Nancy Tobin - Rewa, Natalie (Canadian Theatre Review, 2020)
In this review, I discuss the architectonics of sound composition according to sound artist and designer Nancy Tobin. This chapbook advocates for a comprehensively integrated presence of a sound artist in the processes of rehearsal and espouses a dramaturgy of hearing. Tobin’s distinction between hearing and listening gives forth onto a series of self-studies of her experience of spatial and temporal arrangements presented in the form of e-mails to mentees. Her appreciation for the acoustics of the performance space extends to the composition of sound to be heard (on occasion as boldly interventionist) and the technologies of broadcasting it: the choice and placement of speakers, as well as their interaction with the performers. Tobin argues for a definition of sound composition for performance as a complex collaboration with the production—curatorial in terms of the space of ephemerality. My review concurs with the efficacy of her approach by my recognition of the moments in productions that have remained as some of the most memorable of my theatregoing.
Keywords: Nancy Tobin; acoustic space; rehearsal processes; sonic/acoustic dramaturgy; sound artist; speaker specifications and broadcasting sound

Une approche sensible du son - Bertin, Raymond (Jeu : revue de théâtre, 2019)
Article sur l'artiste sonore Nancy Tobin.

Jouer les femmes : les concerts de musique contemporaine au Québec - Couture, Ariane (Recherches féministes, 2019)

« Cohérence d’une œuvre métissée » : extrait de thèse de doctorat (2007) - Makdissi-Warren, Katia (Circuit, 2019)

Katia Makdissi-Warren : étapes et œuvres marquantes - Pascal, Noémie (Circuit, 2019)

L’univers de Katia Makdissi-Warren (un diagramme) - Pascal, Noémie (Circuit, 2019)

"A Jewish Maestra and a Lady too": Reflections on Femininity in the Career of Ethel Stark - Rachwal, Maria N. (Canadian Jewish Studies, 2019)
Ethel Stark (1910-2012) was one of the most important conductors and concert violinists in Canada in the Twentieth century. This article highlights how an Austro-Canadian Jewish woman who lived outside the constraints of conventional domesticity, both navigated through and defied the ideals of the “Cult of True Womanhood” and spearheads a movement of feminism in music. I argue that Stark’s exposure to Jewish cultural traditions of social justice and womanhood in her childhood formed a critical dimension of her feminist activism later in her life, and in particular in the founding of The Montreal Women’s Symphony Orchestra (1940).

The Expression of the Tragic in the Chamber Cantata Dați-Mi Lampa Lui Aladin [Give Me Aladdin's Lamp] by Dora Cojocaru - Seraz, Roxana Maria (Musicology Papers, 2019)
Dora Cojocaru is recognized as an outstanding representative of the Cluj school of composition, but also as a strong voice in Romanian musicology. While her musicological output includes books, studies, articles, radio programs, conference papers, master classes and scientific communication sessions, her most important contribution remains the book entitled Creația lui Gyӧrgy Ligeti în contextul stilistic al secolului XX [Gyӧrgy Ligeti's Work in the Stylistic Context of the Twentieth Century], which was the first book about Ligeti that appeared in the Romanian musicological landscape. Dora Cojocaru’s compositional portrait can be drawn by following the language characteristics and compositional devices used in the chamber cantata Dați-mi lampa lui Aladin [Give Me Aladdin's Lamp]. The composer’s work is characterised by a propensity for chamber music. The composer confesses that it is also a consequence of the fact that this genre comes with a plethora of expressive possibilities. In terms of the musical language used by the composer, its first characteristic is the concern to avoid repetition in expression and the variation of an already used musical material. This is strikingly evident in the chamber cantata Dați-mi lampa lui Aladin [Give Me Aladdin's Lamp]. Another peculiarity is the construction based on a developmental discourse, while a third characteristic is the frequent construction of the discourse based on an economy of means and on a musical material consisting of only a few notes. In the case of this cantata, it is essential to note the historical context, which is closely linked to the symbolic title suggesting the composer’s desperate desire to bring her brother back to life, although she is aware that this is only possible by magic. The composer’s choice of lyrics is derived from the fact that Trakl’s and Rilke’s texts allude to the theme of death, which is one of the frequent themes of late Expressionism, and are therefore pervaded by a tragic note, in tune with the composer’s musical intentions. If we follow the text-music relationship, we notice some extremely significant moments, in which music creates sonic images that are suggestive of the message of the text.

Reality Sounding: Annesley Black’s not thinking about the elephants - Tan, Anthony (Circuit, 2019)
This paper presents an analysis of Annesley Black’s not thinking about the elephants (2018), for saxophone quartet and live electronics. Written for Montreal’s Quasar Saxophone Quartet, this work explores concepts of suppression and emergence through traditional musical dimensions such as melody, counterpoint, and form, but also through contemporary musical dimensions such as psychoacoustics (difference tones), theatrical elements, and live electronics. Black’s practice engages critically with the compositional process itself by formulating dialectic relationships between material and compositional strategies (both intuitive and systematic). This work encourages the listener to engage in a multidimensional listening experience where conceptual extremes become a catalyst for the building of narrative and tension.

A Landscape of Memories through the Music of Hope Lee - Feliz, Juro Kim (Nomadic Sound Worlds, 2018)
Produced by Juro Kim Feliz under the Canadian Music Centre Library Residency, Nomadic Sound Worlds is a four-part blog/podcast series exploring Canadian contemporary music through the lens of present-day global migration. A collection of essays named Letters of Transit: Reflections on Exile, Identity, Language, and Loss (ed. André Aciman, 1999) informs and inspires this project, with trajectories branching out from related themes including mobility, displacement, loss, reconciliation of polarized truths, and invention of selves. In this regard, the series will feature selected immigrant Canadian composers whose musical worlds collide with various personal stories of immigration.

Ana Sokolović. Robots musicaux et kolo serbe - Harman, Brian (La création musicale au Québec, 2018)

Their Own Agenda: The History, Development, and Culture of Women's Orchestras Outside the United States - Alger, Bonnie Eve (Université du Maryland, 2018)
Women have been active as performers of instrumental music since the Medieval period, and yet their contributions are often overlooked. This dissertation examines the history of women’s orchestras outside the United States, and explores their development, as well as reasons for existing. Several factors regarding their development are taken into consideration, including time period, country, and culture in which the ensemble is present. The birth of the women’s orchestra is traced from the ospedali of the 18th century Venice to today. All-female ensembles from England, Canada, Cuba, and Afghanistan are profiled, as well as the Women’s Orchestra in Auschwitz. Two modern-day women’s orchestras – the Allegra Chamber Orchestra in Vancouver, British Columbia, and my recital orchestra at the University of Maryland – were surveyed in an attempt to learn more about the culture of women’s orchestras. This paper seeks to answer the questions “What is the culture of women's orchestras today, and should they continue to exist?”

Aller à la quête de l’œuvre : Véronique Lacroix et les 30 ans de l’ECM+ - Champagne, Éric (Circuit : musiques contemporaines, 2018)

A Rich Musical Legacy from Québec: Baroque Motets of the Ursuline and Hôtel-Dieu Monasteries of New France - MacIsaac, Elizabeth Kathleen Norah (Université de Washington, 2018)
Carefully preserved in the archives of the Ursuline and Hôtel-Dieu Monasteries of Quebec are several manuscripts containing Canada’s first sacred works for female voices. The manuscripts contain dozens of intricate motets composed in the French Baroque style, a repository of music which has not been sung for hundreds of years. These motets form a neglected part of Canada’s musical heritage which is waiting to be unearthed and explored. Ursuline and Augustinian nuns arrived to the French territories of the New World to educate and evangelize young women. Singing formed a core element of their teaching and worship. For over one hundred years (1639-1760), church music provided a backbone to Canada’s vibrant musical culture. When the French territories were lost to Britain and Spain, musical culture shifted radically and the sacred French music simply faded into obscurity. An overview of the sweeping events of the French Baroque era includes discussion of France’s social conditions, the political and religious climate, the flowering of the arts and the exploration of the New World. In France, the seventeenth and eighteenth centuries were a time of great strife which heralded the massive social changes to come in the nineteenth century. France’s struggles directly impacted the colony of New France, including that of its religious institutions and music. This study traces the musical activities in the Ursuline community of New France as the nuns lived their mission on the frontier, teaching Aboriginal and colonial girls. The evolution of female emancipation stemming from religious evangelism is considered. Examination of a trove of 160 motets located in the female monasteries of Québec City reveals the high caliber of music practiced by the nuns. No interpretive editions for performance purposes exist. Newly transcribed works have been generated from the manuscripts, with period performance guidance for appropriate ornamentation and ensemble requirements. An in-depth discussion of New France Baroque vocal and choral musical styles is provided, with reference to historical records of how it was taught, as described in contemporaneous music treatises and many original documents specific to these religious female communities.

Isabelle Panneton. De la rigueur à la liberté de création - Nattiez, Jean-Jacques (La création musicale au Québec, 2018)

L’apport de Maryvonne Kendergi à la SMCQ - Bail, Louise (Circuit : musiques contemporaines, 2017)
To measure Maryvonne Kendergi’s contributions to the smcq, it is necessary to revisit her career in Quebec, which was based on the solid academic and professional training she received at Parisian institutions from 1929 to 1952. Thereafter, in Montreal, she was hired by Radio-Canada for her exceptional voice, and in September 1956, she embarked on a brilliant radio career as a promoter of contemporary music. Kendergi gradually introduced the listening public to the arcana of the Montreal avant-garde. In this endeavour she was encouraged by Stockhausen’s arrival in Montreal in 1958, by composers’ efforts in organizing International Music Week in 1961, by the foundation of the smcq in 1966, and by the influence of the latter organization, particularly in its collaboration with the Université de Montréal in establishing the Musialogues in 1969. The role of Kendergi’s exceptional skills in broadening the influence of the smcq is explored in this article.
Keywords: Maryvonne Kendergi; Musialogues; Société de musique contemporaine du Québec (smcq); animatrice; host; music journalist; musicographe de radio

D’exil et d’américanitude : un entretien avec Linda Bouchard - Bertrand, Simon (Circuit : musiques contemporaines, 2017)
Quebec composer Linda Bouchard (born 1957) is an extremely prolific composer, particularly active on the new music scene in the u.s. where she has lived for lengthy periods since 1989. She has composed a rich and diverse catalogue of works, ranging from orchestral music to more intimist instrumentations, and also using multimedia or improvisation. In this interview, the composer reflects on the question of exile and identity in light of her own experience, thus reliving her own artistic path while also addressing some still burning questions about the place of music creators in the global culture.
Keywords: composer; compositrice; exil; exile; identity; identité; parcours; society; société; trajectory

Cool Control, Occam, and Océan: The Radigue and Bozzini Game - Majeau-Bettez, Emanuelle (Les Cahiers de la Société québécoise de recherche en musique, 2017)
Cet article analyse la nouvelle collaboration entre la compositrice et pionnière de musique électronique, Éliane Radigue, et le Quatuor Bozzini. Débutant vers la fin des années 1960, la carrière d’Éliane Radigue se caractérise par de très longues oeuvres de musique électronique qui semblent de prime abord ne pas changer, et dans lesquelles les micro-oscillations naturelles entre les hauteurs remplacent la rythmique traditionnelle. Depuis 2001, Radigue ne travaille plus qu’avec des instrumentistes et utilise un « processus de composition intuitif » semblable à la « transmission orale de musiques traditionnelles anciennes » (Sonami 2017). Alors que les quelques intellectuels qui ont fait montre d’intérêt envers la musique de Radigue ont concentré leur attention sur l’aspect oral de ses compositions, cet article cherche ici à amener l’analyse au-delà des paramètres formels « non-écrits » de sa musique afin d’explorer comment la sonorité d’une pièce de Radigue génère de nouvelles manières de concevoir la performance et la composition. Les notes d’observation de l’auteure, la correspondance entre l’auteure, la compositrice et le quatuor, et les enregistrements des rencontres entre les Bozzini et Radigue seront utilisés pour retracer les moments de grande réaction émotionnelle causés par la sonorité très particulière que demande la musique de Radigue. Ces réactions affectives du côté de Radigue et du quatuor révèlent des points de tension entre différentes conceptions de la création collective, et réorientent complètement ce que cela signifie que de posséder, transmettre, interpréter et composer de la musique. Des spectrogrammes et des enregistrements des tentatives entreprises par les Bozzini seront utilisés dans l’étude de ces points de tension, et démontreront qu’afin de pouvoir jouer avec succès une pièce instrumentale de Radigue, les Bozzini doivent reproduire chaque élément des pièces électroniques de la compositrice; le quatuor à cordes doit se « transformer » en un étrange instrument.

Björk Digital : escale à Montréal - Marcotte, Nicolas-Alexandre (Circuit : musiques contemporaines, 2017)
An article from Circuit, on Érudit.

A performer's perspective on three works for pianist and moving images : analysis with performance and practice strategies for Michel van der Aa's 'Transit', Nicole Lizée's 'Hitchcock Études', and 'Surface Tension' by Eve Egoyan and David Rokeby - Morano, Christopher (Université de Colombie-Britannique, 2017)
Interest in audio-visual works of art that are performed by a live pianist while integrating projected moving visual images has waxed and waned over a period of almost 300 years. The past twenty years or so has seen a re-emergence of this genre of classical music composition which places extra demands on the pianist performing these works. This dissertation explores the history of this genre, proposes a framework for analysis of these pieces, and examines from both analytical and performance perspectives three contrasting works for this medium: Michel van der Aa’s 'Transit', Nicole Lizée’s 'Hitchcock Études', and 'Surface Tension' by Eve Egoyan and David Rokeby. This research was

Partition pour femmes et orchestre. Ethel Stark et la Symphonie féminine de Montréal - Rachwal, Maria Noriega (Éditions du remue-ménage, 2017)
En 1940, deux femmes élégantes prennent le thé dans le lobby du Ritz-Carlton. Ne vous fiez pas aux apparences: leur rencontre annonce un grand chambardement dans l’univers de la musique classique. La mécène Madge Bowen et la violoniste Ethel Stark fondent à Montréal ce qui deviendra le premier orchestre symphonique canadien composé uniquement de femmes. […]

Le son au théâtre et en danse contemporaine : les principes conceptuels récurrents de ma pratique - Tobin, Nancy (Université du Québec à Montréal, 2017)
Ce mémoire-création porte sur la conception sonore pour le théâtre et la danse contemporaine. Il vise à fournir des connaissances qui puissent faciliter l'intégration du son au sein d'une création scénique. La recherche dont il est question ici se concentre uniquement sur les aspects conceptuels et non techniques, toutes deux intrinsèques au processus de création du son. Me basant sur mon expérience de concepteure sonore, plus précisément à partir de l'étude de mes notes de chantier de création entre 1999 et 2014, je dégage dix principes récurrents qui indiquent des conditions optimales pour concevoir le son. Ce mémoire-création est l'analyse d'une approche personnelle et le processus méthodologique a été autopoïétique et heuristique. L'étude se présente en trois sections. La première s'intéresse aux récits des processus de création où chaque principe émerge à partir de l'expérience qui est racontée. Dans la deuxième section, les principes s'explicitent davantage au travers l'étude de textes sur la conception du son. Un corpus d'auteurs, surtout des praticiens de la création sonore, est déterminé pour cette partie. Un livret compose la troisième section. Il incarne la partie « création » de ce mémoire. Il s'agit encore de préciser les principes, mais cette fois au travers de dix lettres fictives, destinées à des étudiants-es. Chaque lettre, dont le sujet est un problème rencontré en cours de processus de création, vise à expliquer un principe dans un contexte concret. Le titre du livret est La conception sonore selon Nancy Tobin 01. Mon nom apparaît dans le titre pour signifier qu'il est surtout question de mon approche personnelle. La mention des chiffres « 01 » indique que le livret démarre une série où d'autres personnes conceptrices sont invitées à écrire sur leur propre expérience. Peu de textes sur la conception sonore - sur l'expérience concrète du faire - existent. Ce mémoire-création vise à combler en partie cette lacune et à inviter d'autres créateurs à écrire sur leur pratique. L'expression par le sonore est riche et diversifiée. Plus les pratiques seront partagées et diffusées, plus il sera possible de multiplier les possibles de l'espace de l'écoute.

Bilan et perspectives sur la situation des compositrices au Québec : vers un décloisonnement des identités - Tremblay, Vicky (Les Cahiers de la Société québécoise de recherche en musique, 2017)
In the field of composition in Quebec, women composers are still less numerous than men composers. While the profession of composer has difficulty being recognized in Quebec society, women composers are twice as marginalized. Many of give evidence to the challenges they face when it comes to integrating into the musical community, and several musicologists have tried to better understand—and eventually solve—the problems specific to women in the field of composition.

Animating the Object: Marcelle Deschênes and acousmatic education in Quebec - Valiquet, Patrick (Organised Sound, 2017)
This article examines the early reception of Pierre Schaeffer’s theoretical work in Quebec through the teaching of Marcelle Deschênes, principal author of the first electroacoustic theory and ear training curricula at both Université Laval and Université de Montréal. An account of Deschênes’s educational career is provided, along with remarks on the contents of her early courses in Morpho-typology and her listening workshops for children, using newly excavated primary material from her private archives. While existing scholarship presumes that Schaefferian thinking arrived in Quebec with the ‘orthodox’ acousmatic approach of Francis Dhomont, this article asserts that a pluralist and multidisciplinary interpretation of Schaeffer’s work can be discerned which pre-dated Dhomont’s teaching and has had an equally lasting impact overall. A methodological argument is also made for including education and other forms of ‘reproductive labour’ in the history of electroacoustic music.

Nicole Lizée : adepte de la hantologie - Van Vliet, Kiersten (La Scena Musicale, 2017)

Where Is She? Finding the Women in Electronic Music Culture - Abtan, Freida (Contemporary Music Review, 2016)
The author discusses the visibility and participation of women in electronic music culture. She argues that most electronic music social networks privilege male inclusion and success, and that skill-sharing is an important strategy to encourage women in the field. To seed this discussion, the author examines her own history with reflections on the gender dynamics within electronic music communities outside the academy, and the role that social and technical currencies play within them. She also discusses Ladies club, a music distribution project that led to several solo female electronic musicians taking the stage and organising events in Montreal during 2007.
Keywords: Culture; Electronic Music; Feminism; Gender; Skills-Sharing

Creative layers and continuities: A case study of Nicole Lizée and the Kronos Quartet - Bayley, Amanda; Lizée, Nicole (Musicae Scientiae, 2016)
This study examines the creative layers and continuities evident within the composition and rehearsal processes of Nicole Lizée’s Golden Age of the Radiophonic Workshop (Fibre-Optic Flowers), written for the Kronos Quartet in 2012. Lizée’s compositional approach to the historic and the new, and the mechanical and the human, are interpreted through Simon Emmerson’s three themes of combination, transformation, and control, and his three “impulses within composition” that combine live and acousmatic soundworlds – integration, antithesis, and co-existence. These concepts also help to articulate the way the players engage with the physical, psychological, and expressive demands of the piece. Discussions arising from the Kronos Quartet rehearsing the piece with the composer reveal how extensions are made to the performers’ mind and body experiences when they are required both to initiate and integrate sounds emanating from unfamiliar, analogue machines into their acoustic, yet amplified soundworld. Creative layers and continuities are seen to evolve from compositional experimentation and from composer–performer and co-performer dialogues in rehearsal in the BBC Maida Vale studio prior to the world premiere at a BBC Prom concert on 24 July 2012.
Keywords: Delia Derbyshire; Kronos Quartet; Radiophonic Workshop; composition; creativity; electronic sounds; interaction; notation; rehearsal; string quartet

Le Club musical de Québec : 125 ans - Bernier, Emmanuel (Cap-aux-Diamants, 2016)

The Songs of Violet Archer: Tracing the Evolution of One of Canada's Most Prominent Composers - Dauphinais, Paul (Université de Boston, 2016)
In this study, four sets of songs composed by Violet Archer are examined, all of which were written at different points in her career. Archer studied with Paul Hindemith in 1948 – 49, and his teachings had a tremendous impact on the young composer. The first set of songs to be analyzed, Moon Songs, was written before her time with Hindemith, and will provide a baseline from which her later, post-Hindemith, works can be compared. Following her studies with Hindemith, Archer wrote three songs, “Cradle Song,” “April Weather,” and “First Snow,” all of which show evidence of Hindemith’s influence. Her later, more mature works, Northern Landscape and Caleidoscopio Quatro, demonstrate a refined compositional technique; one in which Archer has created her own style, while maintaining aspects of the approach taught by Hindemith at Yale. This study will elaborate on the aspects of Archer’s music that evolved throughout her compositional career.
Keywords: Archer; Communication and the arts; Hindemith; Music analysis; Paul; Social sciences; Violet

Analyses of Organ Etudes Opp. 38, 66 and 72 by Rachel Laurin - Mateva, Silviya (Université d'Oklahoma, 2016)

Écritures chorégraphiques et sonores imbriquées : récits de collaborations avec Danièle Desnoyers - Tobin, Nancy (L’Annuaire théâtral : revue québécoise d’études théâtrales, 2016)
Ce texte revient sur le processus de création de trois spectacles chorégraphiques auxquels j’ai participé comme conceptrice sonore : Concerto grosso pour corps et surface métallique (1999), Duos pour corps et instruments (2003) et Là où je vis (2007). Ces parcours de recherche-création, traversés avec la chorégraphe Danièle Desnoyers (compagnie Le Carré des Lombes), permettent d’observer comment l’écriture sonore se développe in situ avec l’écriture chorégraphique. Les deux se forment ensemble en s’influençant l’une l’autre. Les trois spectacles choisis témoignent de différents modes de création de la matière sonore : amplification des danseurs, diffusion avec des haut-parleurs inusités, invention d’instruments et citation de musiques transformées. Les récits de collaborations qui suivent révèlent les manières dont la matière sonore a émergé de l’écriture chorégraphique et vice versa.

A Study of Selected Representative Organ Pieces by Rachel Laurin - Cheng, S.S. (Université du Kansas, 2015)
Over the course of the last decade the organ works of Canadian composer Rachel Laurin (b. 1961) have gained critical acclaim among professional organists. Her organ music has captured the attention of American and Canadian organists, resulting in a series of commissions for new organ works. To date, there are over thirty-two compositions for organ solo. This document explores stylistic issues in Laurin's compositions for solo organ and for organ with other instruments. Pieces that have been selected for in-depth study include Chromatic Fantasietta, Scherzetto, Toccatarina (to Katarina) and Asian Legend from Twelve Short Pieces, Volume 3, op. 64, Étude Héroïque, Op.38, and the Sonata for Organ and Horn, Op.60, II. On a Painting by Thomson. At the outset of the document an overview of Canadian organ culture is provided, followed by an introduction to Laurin's life and works. Subsequently, a structural and harmonic analysis of Laurin's compositions is presented. As this analysis will reveal, the expressive dimensions of her works embrace elements of Romanticism and Impressionism.

ECM+ Génération 2014 : regards sur les quatre compositeurs lauréats (1re partie) - Henry, Symon (Circuit, 2015)

ECM+ Génération 2014 : regards sur les quatre compositeurs lauréats (2e partie) - Henry, Symon (Circuit, 2015)

From Kitchen To Carnegie Hall: The Story of the Montreal Women's Symphony Orchestra - Rachwal, Maria Noriega (Second Story Press, 2015)
In the 1940s it was unheard of for women to be members of a professional orchestra, let alone play "masculine" instruments like the bass or trombone. Yet despite these formidable challenges, the Montreal Women's Symphony Orchestra (MWSO) became the only all-women orchestra in Canadian history. Formed in 1940, the MWSO became the first orchestra to represent Canada in New York City's Carnegie Hall and one of its members also became the first Canadian black woman to play in a symphony in Carnegie Hall. While the MWSO has paved the way for contemporary female musicians, the stories of these women are largely missing from historical records. From Kitchen to Carnegie Hall illuminates these revolutionary stories, including the life of the incredible Ethel Stark, the co-founder and conductor of the MWSO. Ethel's work opened doors of equal opportunity for marginalized groups and played an important role in breaking gender stereotypes in the Canadian music world.
Keywords: History / Canada / Post-Confederation (1867-); Music / History & Criticism; Music / Individual Composer & Musician

Marketing, Merch, and Media: Nicole Lizée, in Conversation - Wiseman, Howard; Disman, Adriana (Canadian Theatre Review, 2015)
Nicole Lizée is an award-winning classical music composer and performer who composes for string quartet, electronic music, turntable, film, and other media. She has emerged as a major new voice in new classical composition, winning the coveted Canada Council for the Arts Jules Léger Prize (2013) for new Canadian chamber music with her work White Label Experiment. She has been commissioned by the Kronos Quartet among many other prestigious ensembles. This interview engages her relation to various aspects of her work, from marketing and promotion to inspiration and creation in the context of “avant garde” music. How can marketing continue to be part of the art itself? Does instinctively not fitting into a box allow for greater freedom to explore classical and chamber music in the broader context of film and other media? What other factors may be contributing to the inspired vitality of her work?
Keywords: Entretien

Glimpses Into My Compositional Style and Techniques : Text and Musical Examples - Badian, Maya (Lucian Badian Editions, 2014)

Soprano Pierrette Alarie (1921-2011), tenor Léopold Simoneau (1916-2006). Part 1 - Duffie, Bruce (Opera Journal, 2014)
Keywords: Interviews; Music; Musical performances; Musicians & conductors; Singers

Soprano Pierrette Alarie (1921-2011), tenor Léopold Simoneau (1916-2006). Part 2 - Duffie, Bruce (Opera Journal, 2014)
Keywords: Accompanists; Composers; Librettists; Music; Musical performances; Musicians & conductors; Opera; Singers

Nicole Lizée. Faisceaux imaginaires et cool media - McKinley, Maxime (La création musicale au Québec, 2014)

Layers of creativity in composition, rehearsal and performance: Nicole Lizée and the Kronos Quartet - Bayley, Amanda; Lizée, Nicole (Tracking the Creative Process in Music Second International Conference, 2013)

Le son tactile ou la sensorialité excentrique dans les performances solos de Magali Babin - Abenavoli, Lorella (Circuit : musiques contemporaines, 2013)
How can the ephemeral touch of a caress become an aesthetic object? How can a fingernail scratching the mineral surface of a sheet of schist become music? How can intimate tactile experience become the scene of a collective artistic ritual? How does Magali Babin turn electronic sound into a medium for eccentric sensoriality? This article takes us into one region of Magali Babin’s artistic practice: the tactile world of sound that she uses in her solo performances. Author of a polymorphic sonic oeuvre, Magali Babin is a Quebec artist, performer, and composer whose artistic practice has incorporated sonic installations for the past two years. She is a key figure in Montreal’s alternative audio art, “edgy” improvisation, and experimental music scenes, moving freely among cutting-edge artistic categories.
Keywords: Magali Babin; art audio; art haptique; audio art; device; dispositif; eccentric sensoriality; electronic; haptic art; improvisation; performance sonore; sensorialité excentrique; sonic performance; électronique

Providing the Taste of Learning: Nadia Boulanger’s Lasting Imprint on Canadian Music - Boivin, Jean (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2013)
This article traces the rich Canadian legacy of the twentieth-century French musical legend Nadia Boulanger (1887–1979). Through teaching her more than seventy Canadian students, both French- and English-speaking, the renowned French pedagogue played a crucial role in the development of concert art music in this country from the 1920s, notably in Montreal and Toronto. Her numerous Canadian students went on to distinguish themselves as composers, teachers, performers, musicologists, theorists, administrators, and radio producers. Drawing on extensive archival and primary research, this study demonstrates the decisive impact Boulanger had on the development of musical styles and compositional practices in Canada in the last century.

Du rôle de l'interprète-chercheur en création et re-création musicale : théories, modèles et réalisations d'après les cas de Kathinkas Gesang (1983-1984) de Karlheinz Stockhausen et de La Machi (2007-2011) d'Analía Llugdar - Breault, Marie-Hélène (Université de Montréal, 2013)
Cette thèse est basée sur une approche méthodologique hybride relevant de recherche-création en musique et de musicologie appliquée à l’interprétation. Elle s’intéresse à cette question centrale : « Quels rôles l’interprète-chercheur occupe-t-il dans un contexte de création ou de re-création (ou d’interprétation) musicale » ? Pour y répondre, l’auteure examine et rend compte du processus créateur et re-créateur de deux œuvres significatives dans son parcours en tant qu’interprète, soit Kathinkas Gesang als Luzifers Requiem (1983-1984) de Karlheinz Stockhausen et La Machi, rituel pour flûtes, électronique et regards (2007-2011) d’Analía Llugdar. Le travail de ces œuvres mixtes qui comportent toutes deux une dimension théâtrale tout en mettant en scène des personnages instrumentaux l’amène aussi à traiter des problématiques de l’appropriation de l’œuvre par l’interprète-chercheur et de la liberté de celui-ci face aux œuvres présentant un haut degré de déterminisme notationnel. La première partie situe les contextes disciplinaires et théoriques des recherches de l’auteure. Le premier chapitre permet de comprendre comment s’exerce la recherche de l’interprète en musique et de situer les différentes modalités dans lesquelles ce type de recherche s’effectue. Le deuxième chapitre explique les notions d’interprétation, d’improvisation et de composition et il situe l’interprète par rapport à ces trois champs d’activités. L’auteure y compare aussi les modes créatifs du théâtre à ceux de la musique tout en s’intéressant aux divers types d’authenticité inhérents au travail d’interprétation. Le troisième chapitre pose le principal angle d’investigation et d’analyse adopté dans cette thèse, soit celui du timbre instrumental. La deuxième partie porte sur Kathinkas Gesang de Stockhausen. Le quatrième chapitre présente une chronologie récapitulative des différentes grandes périodes d’appropriation de l’auteure. Le cinquième chapitre présente et met en contexte le symbolisme du cycle Licht, die sieben Tage der Woche (1977-2003), dans lequel Kathinkas Gesang s’insère. Le sixième chapitre est voué à une analyse du symbolisme attribué au timbre des principaux instruments que l’on retrouve dans Licht. Le septième chapitre évalue l’impact de la présence des interprètes dans le processus compositionnel chez Stockhausen tout en traitant de la question du casting dans Licht. Le huitième chapitre s’articule en un lexique timbral présentant une exégèse des techniques de jeu employées dans Kathinkas Gesang pour produire divers types de timbres. La troisième partie porte sur La Machi d’Analía Llugdar. Dans le neuvième chapitre, l’auteure présente la structure générale de l’œuvre et son synopsis et elle traite du rôle qu’elle a joué dans le processus de création de cette œuvre. Le dixième chapitre prend la forme d’un lexique timbral présentant une exégèse des différentes techniques de jeu employées dans l’œuvre pour produire divers types de timbres. Dans la conclusion, trois sphères d’action et six rôles-types de l’interprète-chercheur en création et en re-création musicale sont identifiés. De plus, des réponses aux problématiques de l’appropriation de l’œuvre et de la liberté de l’interprète sont apportées. L’auteure y suggère également des pistes de réflexion pour la recherche- création en musique et elle y présente les principales retombées de la thèse.

« Donner le temps » : entretien avec Lorraine Vaillancourt - Goldman, Jonathan (Circuit : musiques contemporaines, 2013)
In an interview with Lorraine Vaillancourt, the founder and artistic director of the Nouvel Ensemble Moderne (nem) recounts her musical education in Quebec, Montreal and Paris, and goes on to describe the establishment and development of her ensemble, the choice of repertoire and her plans for the future.
Keywords: Lorraine Vaillancourt; Nouvel Ensemble Moderne; contemporary music ensemble; direction musicale; ensemble de musique contemporaine; musical conducting

Faisceaux imaginaires et cool medias : This Will Not Be Televised de Nicole Lizée - McKinley, Maxime (Circuit : musiques contemporaines, 2013)
The imagination of composer Nicole Lizée brings together disparate elements, largely drawn from cinema, philosophy, visual arts, and so-called popular music, with a pronounced penchant for the period from 1960-1980 and the ghostly effect thus conveyed. This article illustrates Lizée’s creative process through one of her characteristic works, This Will Not Be Televised (2005-2007), scored for DJ and seven instruments. Our analysis illustrates how the composer’s “beams of imagination” take form through a unique musical language, based here on a meticulously notated DJ part and extended through the instrumental ensemble, and which draws on cultural references, repetitive effects, and montages of juxtapositions and superpositions, and whose continuous form achieves cohesion through the use of repeats. In this way, the composer focuses on the connections that are generated in the memory and subjectivity of the hearer – the tabula rasa characteristic of McLuhan’s “cool” media.
Keywords: Nicole Lizée; This Will Not Be Televised; analyse; analysis; cool medias; tables tournantes; turntable; “cool” media

Maryvonne Kendergi (1915-2011) : hommage et mémoire - Bail, Louise (Circuit, 2012)

The Vocal Music of Ana Sokolović: Love Songs for the Twenty-First Century - Bernstein, Tamara (Circuit, 2012)
Enchanted by the vocal music of Serbian-born Canadian composer Ana Sokolović, Tamara Bernstein visited the composer at her home in Montreal. Sokolović’s music draws on several sources, including the theatrical world and the culture of the Balkans. The extended vocal techniques in Sokolović’s music are rooted not in the avant-garde music of the twentieth century, but in the oral traditions and poetic voice of Serbia. It seems that the more the composer returns to her cultural roots, the more she embraces the universality of the human soul.

Life notations of Daisy Sweeney: reflections of othermothering, musicianship and Montreal - Campbell, Arlene (Université York, 2012)
The life story of Mrs. Daisy Sweeney, an African Canadian native of Montreal, Quebec, helps fill a void in the historical documentation of Montreal Blacks (especially female elders). Of particular significance is her prominence as a music educator and othermother during her life. The current literature on African Canadian othermothering experiences is not synonymous with both White or African American females and inclusion of their voices in academic, as well as mainstream spaces, is virtually non-existent. This dissertation asks: What did it mean to be a first generation 'Negro' working class bilingual female in a largely hostile White francophone Quebec metropolis in the early 20th Century? How can her narratives help shape and inform life history and African Canadian othermothering research? My sojourn with Mrs. Daisy Sweeney referenced African centered epistemology in my conceptual understanding of herself and community mothering. Capturing her conversations meant engaging with multiple methodologies articulated through African oral traditions, life history, archival canons and interdisciplinary inquiries. It is striking to note that there were not only certain tensions associated with memory loss and physical limitations (prompted by the aging process) that destabilized and enriched our 'interactive' communication, but also revealed a rupture and reversal of the participant/researcher dynamic. In spite of blatant racial discrimination that plagued Montreal's Black communities during that time, Daisy Sweeney fulfilled a life-long dream and taught hundreds of children the canon of classical piano for over 50 years. She lived her voice through her music, finding ways to validate her own identity and empowering others in the process. She used the musical stage as her platform to draw invaluable connections between race, gender, language and social class. Daisy Sweeney's generation of othermothers is dying out and, as the carriers of culture, the urgency to tell their stories must be emphasized. The account respects, reclaims and reflects those voices. It is time to write in African Canadian female elders and diversify the exclusionary genre of life history and archival research.

Introduction : la voix d’Ana Sokolović - Goldman, Jonathan (Circuit, 2012)

Musical Robots and the Serbian Kolo: A Narrative Analysis of Ana Sokolović’s Géométrie sentimentale (1997) - Harman, Brian (Circuit, 2012)
Composer Ana Sokolović divided her instrumental work Géométrie sentimentale into large sections inspired by pure geometric shapes — Triangle, Cercle and Carré — describing these sections as three contrasting perspectives of the same musical materials. This article uses a narrative analytical approach as a lens through which to understand these distinct sections and the materials populating them. Inspired by Sokolović’s employment of musical objects in her compositions and by the extra-musical concepts inspiring many of her works, this analysis uses a collection of colourful robot toys as metaphors for the work’s materials. Three unique perspectives of these toys are described: in Triangle, the robots interact as characters on a dramatic stage; in Cercle, they peacefully coexist in slow motion; and in Carré new combinations of robot elements are abruptly juxtaposed against each other. The characteristics and interactions between these toys, as well as the various harmonic ‘masks’ that the composer has them wear, are helpful in understanding Sokolović’s harmonic structure, variation/transformation techniques, formal organization and rhythmic characteristics. The Serbian kolo is also shown as influential on the work, relating directly to the physicality and kinetics of the metaphorical robots.

Choral, Public and Private Listener Responses to Hildegard Westerkamp's École - McCartney, Andra; McCarthy, Marta (Music and Arts in Action, 2012)
Hildegard Westerkamp's (1990) composition École Polytechnique is an artistic response to one of Canada's most profoundly disturbing mass murders, the 1989 slaying of fourteen women in Montreal, Quebec. Using the theoretical model, derived from Haraway, of the cyborg body, and analyzing the import of the mixed media (voices, instruments and electroacoustic tape) incorporated in the music, the authors examine the impact this work has had on some of those who have heard it and performed it, based on the responses of choristers and listeners in several studies. The authors explored how those who engaged significantly with the music, (including those who had no personal association with the actual events of the 1989 massacre), were able to make relevant connections between their own experience and the composition itself, embrace these connections and their disturbing resonances, and thereby experience meaningful emotional growth.

Cartographie de l’apprentie - Messier, Anne (Circuit, 2012)
La compositrice québécoise Ana Sokolović est d’origine serbe et plusieurs de ses oeuvres font référence à son pays d’origine, que ce soit par l’utilisation de mélodies et de rythmes traditionnels ou par des références culturelles. Pour approfondir son héritage serbe, l’auteure s’est entretenue avec la compositrice en mars 2012. L’article relate les paysages de son enfance et de son adolescence, l’environnement musical, culturel et politique de ses années d’apprentissage. Le portrait de sa vie familiale et de son quotidien nous permet de saisir des éléments constituants de sa personnalité d’artiste en devenir. Sa décision de s’établir à Montréal est explorée et elle raconte comment elle a pris conscience de son héritage slave.

« J’aime quand on explose de joie ! » : entretien avec Ana Sokolović - Panneton, Isabelle (Circuit, 2012)
Lors d’un entretien réalisé par la compositrice Isabelle Panneton, Ana Sokolović discute de ses inspirations, de ses méthodes et de son rapport avec les interprètes de sa musique.

L'intuition de/dans l'œuvre de la compositrice québécoise Isabelle Panneton: un défi à la bipartition du genre - Stévance, Sophie (Le genre à l'œuvre, 2012)

Violet Archer's "The Twenty-Third Psalm" (1952): An Analytical Study of Text and Music Relations Through Fibonacci Numbers, Melodic Contour, Motives, and Piano Accompaniment - Wan, Jessica Jane (Université d'Ottawa, 2012)
This study explores text and music relations in Canadian composer Violet Archer's “The Twenty-Third Psalm” by analysing the text of Psalm 23, Fibonacci numbers, melodic contours, motives, and the role of the accompaniment. The text focuses on David's faith in God and his acceptance of God as his shepherd on earth. The four other approaches allow us to examine the work on three different structural levels: background through Fibonacci numbers, middleground through melodic contour analysis, and foreground through motivic analysis and the role of the accompaniment. The measure numbers that align with Fibonacci numbers overlap with some of the melodic contour phrases, which are demarcated by rests, as well as with the most important moments at the surface level, such as the emphasis on the word “death” through recurring and symbolic motives. The piano accompaniment further supports these moments in the text.
Keywords: Archer; Canadian music; Communication and the arts; Fibonacci numbers; Melodic contour; Motivic analysis; Music analysis; Psalm 23; Text and music relations; The Twenty-Third Psalm (1952); Theory; Violet

Entretien avec Isabelle Panneton - Lefebvre, Marie-Thérèse (Les Cahiers de la Société québécoise de recherche en musique, 2011)
Sous forme d’entrevue, la compositrice se remémore les moments importants des cours d’analyse de Gilles Tremblay, plus particulièrement sa manière d’aborder le rapport de la poésie et de la musique, ainsi que son souci du traitement vocal, une approche qui se démarque par son caractère instinctif et sa vision organique des oeuvres. La compositrice parle également de sa propre approche de la poésie et présente quelques-uns de ses projets.

La poétesse de l'ombre [entretien avec l'artiste sonore Nancy Tobin] - Siaud, Florent (Théâtre/Public, 2011)

"Give Me Aladdin's Lamp”: A Possible Perspective of Modernism - Ştefan, Angi (Musicology Papers, 2011)
Defining the differentiated semantics of new and novelty, reversing the dictum non nova sed nove into non nove sed nova, the author of the chamber cantata „Give me Aladdin’s lamp” is based on the rich experience of leading myriad of mid-century modernism. The investigation of the paradigms of new relationships between vocal and instrumental in creation of Dora Cojocaru, is directed in present at the chamber cantata for mezzo-soprano, brass quintet and percussion on lyrics by Emil & Dan Botta, Georg Trakl, Rainer Maria Rilke and Ady Endre (1998). The relations text - melody by their phenomenological reduction to fruitful combinations between poetic word - musical sound in Dora Cojocaru’s cantatas represent a stylistic-rhetorical subsumption of autochthonous and foreign experiences in promoting new compositional and interpretive skills meant for adaptation of appropriate musical expression in portraying contemporary aesthetic message. They are designed on the wide range of contemporary aesthetic values from the grotesque in nascendi to the absurd in morendi. As long as the Cantata Galgenlieder in der Nacht with lyrics by Christian Morgenstern (1995) is conceived at the grotesquely pole on the axis of the field of contemporary aesthetics, the Cantata Give me Aladdin’s lamp is designed in the sphere of the tragic. In the composer’s vocal and instrumental creation (and not only in them) the experiences of today’s musical composition and interpretation are rethought creatively, suggesting in perspective the permanence of modern horizons.

Le 'principe de contrainte stimulante' dans l'œuvre de la compositrice Isabelle Panneton - Stévance, Sophie (Médecine des arts, 2011)

Être compositeur aujourd'hui : entretien de Sophie Stévance avec Isabelle Panneton - Stévance, Sophie (Composer au XXIe siècle. Pratiques, philosophies, langages et analyses, 2010)

Quelle place pour les femmes dans la création musicale au XXIe siècle ? - Stévance, Sophie (Composer au XXIe siècle. Pratiques, philosophies, langages et analyses, 2010)

Reprise et intertextualité musicale. L’hommage à La Bolduc par des compositrices engagées vers l’avant - Stévance, Sophie (Volume ! La revue des musiques populaires, 2010)
Cet article étudie la notion de reprise sous l’angle de l’Hommage à La Bolduc rendu par sept compositrices à Mary Travers (alias La Bolduc), icône de la musique populaire au Québec dans les années 1930, à l’occasion du Festival SuperMicMac. Par des allusions, des références précises et explicites ou par de simples emprunts et citations, ces hommages sont autant de lectures que de relectures des chansons sélectionnées en abordant différents modes de jeux d’«  intertextualité musicale  ». Celle-ci se situe à deux niveaux  : le pôle de la production, qui montre que les chansons engagées de La Bolduc sont elles-mêmes le témoignage d’une époque  ; le pôle de la réception, pour exposer les résonances de ces chansons à partir de références autres et communes à la fois, comme la place des femmes dans la création musicale. Cette étude envisage ainsi la reprise à partir des aspects, des significations et des enjeux musicaux posés par l’intertextualité musicale, ici abordée sous l’angle de l’hommage alors conçu comme «  réactivateur  » de sens.
Keywords: concert / live / festival; féminité / masculinité / genre; intertextualité (musicale); politique / militantisme; reprise / pastiche / parodie; réception

Canadian Women Composers in Modernist Terrain: Violet Archer, Jean Coulthard and Barbara Pentland - Danielson, Janet (Circuit, 2009)
The successful compositional careers of Jean Coulthard, Barbara Pentland, and Violet Archer spanned all but the first three decades of the twentieth century. Entering a compositional career at this time had many challenges: as Western Canadians, these composers had to establish their credibility with a public that could not be counted on to recognize the worth of their work due to sexist bias and a prevailing critical stance: public approval was evidence of a lack of true creativity. This was especially problematic for women, who had to keep to the center of progressive composition, away from the experimental and conservative margins, in order to gain recognition. Following World War II, the pressure of modernism increased, due at least in part to initiatives by the U. S. Government in occupied Germany, countering the stereotype of the unsophisticated American with a new narrative of American experimental tradition.

The Piano Sonatas of Violet Archer: The Creative Influences of Bartók and Hindemith - Friesen, Darryl Shane (Université de l'Illinois à Urbana-Champaign, 2009)

Introduction : Compositrices sur la scène contemporaine - Goldman, Jonathan (Circuit: Musiques contemporaines, 2009)

Micheline Coulombe Saint-Marcoux et Marcelle Deschênes : pionnières dans le sentier de la création électroacoustique - Lefebvre, Marie-Thérèse (Circuit : musiques contemporaines, 2009)
A review of “masculine” and “feminine” attitudes towards music composition of the past fifty years highlights the contributions of Micheline Coulombe Saint-Marcoux and Marcelle Deschênes to the development of Québécois electroacoustic music. The author re-creates the historical context for the composers’ childhoods, adolescences, and periods of training in Montreal and Paris, and follows this with a discussion of how they negotiated the dominant trends of the 1970s. She then turns to the composers’ roles as pioneers: in their wish to depart from well-trodden paths, Coulombe Saint-Marcoux and Deschênes turned to new technological tools that would allow them to express a new artistic sensibility. From this perspective, they should be considered the “sherpas” of Québécois electroacoustic music.

Des pratiques d’artistes et de chercheuses en écologie sonore - Piché, Claire (Recherches féministes, 2009)
This article is an incursion into the domain of sound ecology based on interdisciplinary research about artists and researchers. We expose the fundamental principles of sound ecology, a discipline that emerged during the seventies, and discuss the best practices of women in sound ecology, demonstrating how this constitutes a relevant research area for women’s studies. The link between feminism and sound ecology being established, we summarize three sociopolitically relevant research projects whose methods resemble feminist action research. We conclude by reflecting on the best means to foster interdisciplinary collaboration.

De la musique de geste à la musique du son, de SuperMémé à I8U - Prévost, Hélène (Circuit, 2009)
La musique actuelle née au tournant des années 1970-1980 a connu ses heures de gloire pendant de nombreuses années. Trois femmes font partie de la lancée et demeurent à ce jour des musiciennes actives et des administratrices hors pair. Mais d’autres, artistes sonores plutôt qu’instrumentistes, émergent, au moment du tournant technologique et plus particulièrement au milieu des années 1990. Un nombre important de ces femmes développent des pratiques non instrumentales d’art audio, de musique bruitiste, de musiques mixtes, électroniques expérimentales, d’installation et de multimédia. Elles sont mal connues, méconnues des grands médias et de la plupart des lieux d’enseignement de la musique, bien que plusieurs d’entre elles les aient fréquentés. Ce moment de rencontre avec certaines d’entre elles souhaite les faire apparaître, en plein jour.

Interpreting success and failure: the eclectic careers of Eva and Juliette Gauthier - Slominska, Anita (Université McGill, 2009)
My dissertation explores the eclectic singing careers of sisters Eva and Juliette Gauthier. Born in Ottawa, Eva and Juliettte were aided in their musical aspirations by the patronage of Prime Minister Wilfred Laurier and his wife Lady Zoë. They both received classical vocal training in Europe. Eva spent four years in Java. She studied the local music, which later became incorporated into her concert repertoire in North America. She went on to become a leading interpreter of modern art song. Juliette became a performer of Canadian folk music in Canada, the United States and Europe, aiming to reproduce folk music “realistically” in a concert setting. My dissertation is the result of examining archival materials pertaining to their careers, combined with research into the various social and cultural worlds they traversed. Eva and Juliette’s careers are revealing of a period of transition in the arts and in social experience more generally. These transitions are related to the exploitation of non-Western people, uses of the “folk,” and the emergence of a cultural marketplace that was defined by a mixture of highbrow institutions and mass culture industries. My methodology draws from the sociology of art and cultural history, transposing Eva and Juliette Gauthier against the backdrop of the social, cultural and economic conditions that shaped their career trajectories and made them possible.

Tunes That Bind: Paul J. Seelig, Eva Gauthier, Charles T. Griffes, and the Javanese Other - Spiller, Henry (Journal of the Society for American Music, 2009)
The powerful concept of orientalism has undergone considerable refinement since Edward Said popularized the term with his eponymous book in 1978. Orientalism typically is presented as a totalizing process that creates polar oppositions between a dominating West and a subordinate East. U.S. orientalisms, however, reflect uniquely North American approaches to identity formation that include assimilating characteristics usually associated with the Other. This article explores the complex relationship among three individuals—U.S. composer Charles T. Griffes, Canadian singer Eva Gauthier, and German-trained Dutch East Indies composer Paul J. Seelig—and how they exploited the same Javanese songs to lend legitimacy to their individual artistic projects. A comparison of Griffes's and Seelig's settings of a West Javanese tune (“Kinanti”) provides an especially clear example of how contrasting approaches manifest different orientalisms. Whereas Griffes accompanied the melody with stock orientalist gestures to express his own fascination with the exotic, Seelig used chromatic harmonies and a chorale-like texture to ground the melody in the familiar, translating rather than representing its Otherness. The tunes that bind Griffes, Gauthier, and Seelig are only the raw materials from which they created their own unique orientalisms, each with its own sense of self and its own Javanese others.

La composition musicale et la marque du genre : l’examen conscient de l’« écriture féminine » - Stévance, Sophie (Circuit, 2009)
Si les spéculations idéologiques concernant les différences biologiques entre les sexes persistent dans le domaine de la création, elles ont été mises en valeur dès 1970 par des écrivaines et plasticiennes pour oeuvrer en fonction de mythes spécifiques touchant à leur féminité, au corps de la femme chargé de stigmates, afin qu’émerge un « art féminin ». D’une certaine manière, des compositrices vont emprunter cette voie en affirmant entretenir un rapport différent de celui des hommes à l’écriture musicale. Selon elles, leur sensibilité spécifique et leur situation d’être au monde les poussent à travailler autrement, à partir de thématiques « existentielles » inspirées de leur condition sociale et culturelle. De telles circonstances ont provoqué cette quête identitaire par l’invention d’un style artistique particulier qui, paradoxalement, use de ce qui était considéré par un féminisme radical comme les pièges de la féminité. Cet article tente de montrer que ces spécificités, du moins ces constantes relevées par les créatrices expliquant leur démarche, sont le résultat de recherches esthétiques pour caractériser une création universelle au féminin, et non le produit de diktats biologiques.

Réactiver le sens de l’hommage : L’exemple du Festival SuperMicMac au Canada - Stévance, Sophie (Itamar, 2009)
Cet article étudie la notion d’hommage à partir du Festival SuperMicMac organisé en 2000 par sept compositrices à la mémoire de Mary Travers (alias La Bolduc), icône de la musique populaire au Québec dans les années 1930. Par des allusions, des références précises et explicites ou par de simples emprunts et citations, ces hommages sont autant de lectures que de relectures des chansons sélectionnées en abordant différents modes de jeux d’« intertextualité musicale ». Celle-ci se situe à deux niveaux : le pôle de la production, qui montre que les chansons engagées de La Bolduc sont ellesmêmes le témoignage d’une époque ; le pôle de la réception, pour exposer les résonances de ces chansons à partir de références autres et communes à la fois, comme la place des femmes dans la création musicale. Cette étude envisage ainsi l’hommage à partir des aspects, des significations et des enjeux musicaux posés par l’intertextualité musicale. L’hommage est ainsi conçu comme un « réactivateur » de sens.

Colette Boky. Le chant d'une femme - Boky, Colette; Barrière, Mireille (Éditions Triptyque, 2008)
La présente biographie relate une carrière riche, autant à l'opéra qu'au concert et en récital. Le lecteur pénètre dans les coulisses parfois mystérieuses des maisons d'opéra. Colette Boky nous entretient de ses relations avec ses collègues, de sa conception des principaux rôles qu'elle a incarnés, de ses prestations devant maints personnages célèbres. Mais, plus encore, ces pages tracent le portrait d'une femme résolue, fonceuse, au franc parler, qui ne craint pas de mettre sa réputation au service de causes qui lui tiennent à coeur.

Les femmes et la vie culturelle à Québec avant la Révolution tranquille - Harvey, Fernand (Cap-aux-Diamants : la revue d'histoire du Québec, 2008)

La faim Artaud. Le corps musical éclaté : à la recherche d'un langage musical inspiré d'Artaud - Llugdar, Analia (Université de Montréal, 2008)
Ce travail s'inscrit dans une rechcerche interdisciplinaire tendant à faire le point sur l'actualité de la pensée d'Antonin Artaud à travaers l'analyse du texte radiophonique Pour en finir avec le jugement de dieu. Ce texte conçu peu avant sa mort réunit tous les éléments propres à la pensée d'Artanud tant au niveau philosophique qu'au niveau formel: le corps sans organes, le concept de jugement, l'idée de dieu mais aussi les «sonorisations», les cris et les «glossolalies» à travers une étude profonde des différents textes d'Artaud ainsi que de ses dessins, de sa voix enregistrée, de ses mises en scènes et des différents aspects de son langage, j'ai élaboré une écriture musicale qui m'a permis de composer une oeuvre qui s'inscrit dans le domaine du théatre musical et qui se veut une lecture personnelle d'Artaud. Ainsi, les éléments de ce nouveau langage ont été incorporés aux oeuvres que j'ai composé postérieurement. Nous aborderons dans le chapitre 1 les sourecs nombreuses et hétéroclites du langage d'Artaud; la lecture de ses différentes manières d'expression artistique sont indispensables à la compréhension et à l'interprétation de sa pensée. Le chapitre 2 présente une analyse approfondie de la pièce résultat de ces recherche: La Faim d'Artaud, oeuvre de théatre musical pour sept instrumentistes, mezzo-soprano, baryton, un comédien et une bande pré-enregistrée. Cette analyse montre différents aspects du langage artaudien, présents dans la musique et dans les choix de mise en scène. Le dernier chapitre est une exemplification de l'influence qu'a exercée le langage développé à travers la composition de La Faim d'Artaud dans d'Autres oeuvres de mon répertoire. Pour démontrer cette influence, j'ai réalisé une analyse sommaire de la pièce Todos los recuerdos presentes envolvìan ese sonido y algo me miró pour orchestre de chambre de quinze instrumentistes.

Culture, État et responsabilités : entretien avec Ana Sokolovic - Gendreau, Philippe (Liberté, 2007)

Itinéraire de quatre pionnières de la vie culturelle à Québec après 1945 - Harvey, Fernand (Les cahiers des dix, 2007)
À Québec comme partout ailleurs, la place des femmes dans la sphère publique est relativement récente. L’idée qu’une femme puisse poursuivre des études universitaires, travailler à l’extérieur de la maison ou entreprendre une carrière après le mariage a commencé à se généraliser peu avant les années 1960. Dans ce long cheminement, certaines femmes ont joué un rôle pionnier. Cet article examine le parcours de vie de quatre de ces femmes qui ont réussi à faire leur marque dans le milieu culturel et médiatique de la ville de Québec au cours des années qui ont suivi la seconde guerre mondiale : Francoise Larochelle-Roy, Simone Bussières, Georgette Lacroix et Monique Duval. L’itinéraire biographique de ces pionnières permet de mieux comprendre les singularités de leur insertion dans le milieu culturel et professionnel, en même temps que les points communs qui les relient toutes quatre au contexte d’une époque. On les suivra donc depuis l’enfance jusqu’à la vie adulte où elles évolueront dans l’enseignement, le journalisme, l’animation radiophonique, ainsi que dans le monde des lettres.

Jeanne Maubourg (1875-1953) : l’apprentissage de la modernité théâtrale - Robert, Lucie (Jeu. Revue de théâtre, 2007)
Un article de la revue Jeu, diffusée par la plateforme Érudit.

L’opéra pour enfants ou la quête d’identité : commentaire critique sur L’arche, d’Isabelle Panneton et Anne Hébert - Champagne, Éric (Circuit : musiques contemporaines, 2006)
Avant de rendre compte de l’opéra pour enfants L’arche (musique d’Isabelle Panneton, livret d’Anne Hébert), créé le 25 novembre 2004 par le Nouvel Ensemble Moderne et l’Atelier lyrique de l’Opéra de Montréal, cet article replace l’oeuvre dans un contexte plus large en esquissant un portrait de l’opéra pour enfants au XXe siècle. À travers diverses incarnations (parmi lesquelles l’opéra interprété par et pour des enfants), le genre est caractérisé par une durée limitée à moins d’une heure et un sujet spécifiquement destiné aux enfants, rendu aussi compréhensible que possible par un livret écrit dans la langue de son auditoire et porté par une musique claire et simple. Si ces caractéristiques ne vont pas sans soulever quelques questions, l’auteur estime qu’ils trouvent dans L’arche une illustration tout à fait réussie.

Gender, Genre and Electroacoustic Soundmaking Practices - McCartney, Andra (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2006)
This article is an exploration of how genres and practices of electroacoustic soundmaking are gendered, examining processes of gendering in language used in the early dichotomous categorization between musique concrète and elektronische Musik, then thinking about related arguments concerning abstraction, context, and compositional control in the writings of electroacoustic soundmakers including Pierre Schaeffer, Pierre Boulez, Daphne Oram, Pauline Oliveros, and several participants of the In and Out of the Sound Studio project. Analysis of their practices and ideas suggests different ways of conceptualising electroacoustic genres, their related practices, and roles of contemporary electroacoustic soundmakers (composers, artists, producers, mixers, audiences...), by examining the potentials of the concepts of empathetic knowledge and ecological thinking advanced by feminist epistemologist Lorraine Code.

Portrait d’Ana Sokolovic - Picard, Isabelle (Circuit : musiques contemporaines, 2006)
An article from Circuit, on Érudit.

Œuvres principales d’Ana Sokolovic - Picard, Isabelle (Circuit : musiques contemporaines, 2006)
An article from Circuit, on Érudit.

La alegría de hacer música contemporánea: entrevista con Lorraine Vaillancourt [La joie de faire de la musique contemporaine : entretien avec Lorraine Vaillancourt] - Stan, Luana (Doce notas preliminares, 2006)

Entretien avec Joane Hétu - Arroyas, Frédérique (Critical Studies in Improvisation / Études critiques en improvisation, 2005)

Y a-t-il des créatrices en musique au Québec ? - Carignan, Nicole; Leblanc (FAMEQ à la une, 2005)

Constructions of Identity in the Life Stories of Emma Albani and Glenn Gould - Elliott, Robin (Journal of Canadian Studies, 2005)
Biographical accounts of musicians have enjoyed widespread popularity since the late-Victorian era. Literary theory has recently held biography to be a literary construct, rather than a factual enterprise. Biographies and music are both governed by narrative structures and help to create a sense of individual and collective/national identity. Biographical accounts of two Canadian musicians—Emma Albani and Glenn Gould—are examined. Both musicians are Canadian national icons, but there are several problematic issues in their life stories: Albani’s elitism, class consciousness, and ambiguous relationship to Canada, and Gould’s eccentricity and uncertain sexual identity. The article examines how these issues have been handled in various auto/biographical accounts of the two musicians.

The Loudspeaker as Instrument: the soundworks of Nancy Tobin - Friz, Ann (Musicworks, 2005)

Violet Balestreri Archer (1913-2000) - Hartig, Linda (Music Reference Services Quarterly, 2005)
Violet Archer, one of Canada's well-known composers, passed away in 2000. This article is meant to add biographical information not previously available and to bring closure to her works list. Selected bibliographical citations are also included.
Keywords: Canadian composers; Violet Balestreri Archer

La contribution des femmes à l’histoire musicale et les compositrices d’aujourd’hui au Québec - Lefebvre, Marie-Thérèse (L'accès des femmes à l'expression musicale. Apprentissage, création, interprétation. Les musiciennes dans la société contemporaine, 2005)

L’art de chanter… au féminin : de la prise de paroles au jeu de références postmodernes - Oberhuber, Andrea (L’accès des femmes à l’expression musicale. Apprentissage, création, interprétation : les musiciennes dans la cité, 2005)

Diane Leboeuf: from mixing boards to museums - Gasior, Lisa; McCartney, Andra (Musicworks, 2004)

Geneviève Gilardeau : le violon baroque et Jean-Marie Leclair - Melançon, Johanne (Liaison, 2004)

Étude sociologique de la musique actuelle du Québec : le cas des Productions Supermusique et du Festival International de Musique Actuelle de Victoriaville - Robineau, Anne (Université de Montréal, 2004)
Cette thèse a pour but l’étude sociologique de la musique actuelle au Québec. La musique actuelle est une pratique de création créée en dehors des institutions académiques et des centres de recherche. La professionnalisation de ce milieu artistique est décrite et analysée dans une perspective sociologique en prenant les cas des Productions Supermusique et du label DAME ainsi que du festival International de Musique Actuelle de Victoriaville. L’objectif de cette thèse est d’acquérir une connaissance sur la façon dont s’est développé ce milieu musical des années 70 à aujourd’hui.

Violet Archer: Eine sozio-kulturelle Einordnung der Musik der kanadischen Komponistin unter besonderer Ber cksichtigung der Orchesterwerke [Violet Archer : une classification socioculturelle de la musique de la compositrice canadienne, avec une attention particulière à ses œuvres orchestrales] - Glathe, Kerstin (Université de la Ruhr à Bochum, 2003)
Keywords: Pas de lien web

Creating and Contributing: The Expansive Spirit of Marcelle Deschênes - Mountain, Rosemary (Musicworks, 2003)

Maya Badian: Her Life and Her Music, A Privilege to Soar - Popovici, Fred (Editura Muzicalǎ, 2003)

Maryvonne Kendergi. La musique en partage - Bail, Louise (Éditions Hurtubise, 2002)

New Games in the Digital Playground: Women Composers Learning and Teaching Electroacoustic Music - McCartney, Andra (Feminism & Psychology, 2002)

Québec, vingtième siècle : La création musicale, une affaire de femmes ? - Galaise, Sophie (Musicanada 2000: A Celebration of Canadian Composers/Un hommage aux compositeurs canadiens, 2001)

Les chants sacrés des Ursulines de Québec à l'époque de Marie Guyart - Courville, Louise (Marie Guyard de l’Incarnation. Un destin transocéanique (Tours, 1599-Québec, 1672), 2000)

Colloquy/Débat: Violet Archer, Jean Coulthard, and Barbara Pentland Remembered - Deaville, James (Canadian University Music Review, 2000)
In a bizarre coincidence, three important Canadian women composers from the same generation recently died within five weeks of each other: Barbara Pentland on 6 February 2000, Violet Archer on 22 February 2000, and Jean Coulthard on 9 March 2000. As a tribute to their lives and work, this colloquy gathers remembrances of them by friends and colleagues, ranging from brief anecdotes to extended memoirs. It is thus a collection of primary documents, which yield many new insights into the lives of our composers, ranging from personal habits to the way they taught composition.
Keywords: Canadian music; Careers; Composers; Composition; Music

L’énigme de la correspondance d’Albani à Heugel - Langlois, Maryse (Les Cahiers de la Société québécoise de recherche en musique, 2000)

Quarante ans au cœur de l'Orchestre symphonique de Montréal - Lyse, Vézina (Varia, 2000)

Emma Albani - Vachon, Pierre (Éditions Lidec, 2000)
Biographie concise sur la carrière d'une illustre compatriote, Emma Lajeunesse dite Albani. Elle fut la première cantatrice québécoise à connaître une renommée internationale.

La carrière d’Emma Albani au Covent Garden de Londres - Vachon, Pierre (Les Cahiers de la Société québécoise de recherche en musique, 2000)

Sérieuse, audacieuse, bienheureuse... Généreuses! Rencontre avec Isabelle Panneton, Marie Pelletier et Ana Sokolovic - Davoine, Françoise (Circuit : musiques contemporaines, 1999)
In this exchange with three women composers, Françoise Davoine draws a portrait of their risks, anguish and preoccupations. The speaking-style of the text has been preserved here, giving freshness to the statements as each woman talks about her situation, and the creative process, etc.

Ana Sokolovic : entrevue avec Jean Lesage - Lesage, Jean (Présence de la musique québécoise. Vingt-deux portraits instantanés, 1999)

À propos de cinq œuvres symphoniques de Linda Bouchard - Nattiez, Jean-Jacques (Présence de la musique québécoise. Vingt-deux portraits instantanés, 1999)

Isabelle Panneton : à contretemps - Panneton, Isabelle (Présence de la musique québécoise. Vingt-deux portraits instantanés, 1999)

Estelle Lemire : portrait de l'artiste-compositeure - Provost, Serge (Présence de la musique québécoise. Vingt-deux portraits instantanés, 1999)

Maureen Forrester: Canada's Charming Contralto :a Biography for Young People - Roy, Lynette (Orchid Communications, 1999)

Linda Bouchard : la musique de Linda Bouchard - Tourigny, Maurice (Présence de la musique québécoise. Vingt-deux portraits instantanés, 1999)

Dr. Violet Balestreri Archer, Her Life, Her Vocal Literature, and Her Influence on Contemporary Canadian Music - Valente, Liana Elsie (Université de Caroline du Sud, 1999)
Keywords: Pas de lien web

La contribution des femmes à l’histoire de la musique au Québec - Lefebvre, Marie-Thérèse (New Sound, 1998)
Lors d'un colloque international sur les femmes et la création musicale organise par I'Unesco en mars 1996, Mme Zaimont et Mme Ostleitner des Etats-Unis et de I'Autriche, ont démontré dans leur conférence respective à quel point la vie musicale des pays qu'elles représentent est encore puissamment dominée par les forces conservatrices et traditionnelles I'Autriche plie sous le poids d'un héritage musical ancestral alors que les Etats-Unis (et jusqu'a un certain point le Canada anglophone) vit actuellement au rythme des tendances politiques de droite. Plusieurs des acquis du mouvement féministe sont actuellement remis en question dans les milieux décisionnels et on ne peut que s'inquiéter de I' impact que pourraient avoir ces mouvements conservateurs sur la création musicale des femmes de ce pays. Mais dans ce même colloque, nous avons également pu entendre les propos de représentantes d'autres pays, je pense ici à la Corée, au Japon, à la Bolivie, à I'Uruguay où les femmes prennent une place de plus en plus importante dans le discours musical et dans la production artistique. De son côté, Le Québec, peut-être a cause de sa situation linguistique et culturelle minoritaire, a développé au cours de son histoire une vitalité artistique enviable et a été a I'avant-garde dans plusieurs domaines dont la création musicale. Le réseau de solidarité que les femmes ont bâti dans le milieu musical depuis quelques années et la place que les compositrices occupent aujourd'hui témoignent de cette vitalité.

“Outside in the Machine”: Institutional Experiences and Strategies of Canadian Women Electroacoustic Composers - McCartney, Andra (Ghosts in the Machine: Women and Cultural Policy in Canada and Australia, 1998)

The Solo Piano Music of Violet Archer: A Study of Selected Didactic Works - Willoughby, Angela Sue (Université d'État de Louisiane, 1998)

Répertoire des œuvres des compositrices du Québec au XXe siècle - Labelle, Nicole (Centre de recherche en civilisation canadienne-française, 1997)

Emma Albani. La diva, la vedette mondiale - Labrèche-Larouche, Michelle (XYZ, 1997)
La vie de la célèbre cantatrice canadienne-française qui, au XIXe siècle, conquit l’Europe et l’Amérique et fut l’amie de la reine Victoria et de célèbres compositeurs tels Liszt et Brahms.

Vicissitudes - Maidanik, Victoria (Université McGill, 1997)
Vicissitudes is a composition for orchestra with a duration of approximately 13$ sp prime$ 30$ sp{ prime prime}$. The main idea of the piece, the subdivision of the orchestra into small soloistic groups along with larger ensembles, was inspired by the principles of one of the Baroque forms, namely the Concerto Grosso.

À la manière des préludes non mesurés - Panneton, Isabelle (Circuit : musiques contemporaines, 1997)
Faisant état de l’influence sur elle du répertoire baroque, la compositrice montre quel rôle de modèle ont joué pour elle les préludes non mesurés de Rameau et Couperin, notamment dans son oeuvre Trait, Écart, Réparties. Elle en indique ensuite les prolongements dans quelques autres pièces.

Calme, étale, la mer berce un grand soleil fauve et Quel bruit fait l’arbre qui tombe dans un bois où il n’y a personne pour l’entendre ? - Hébert-Tremblay, Suzanne (Université de Montréal, 1996)

Le rapport inconnu. Quatorze femmes canadiennes dans le studio d'électroacoustique. Seconde partie : compositrices de Montréal et Waterloo - McCartney, Andra (Contact!, 1996)
Keywords: Pas de lien web

Albertine Morin-Labrecque : pionnière dans le domaine de la pédagogie musicale au Québec au XXe siècle - Simard, France (Études en musique des futur(e)s diplômé(e)s du Département de musique de l'Université du Québec à Montréal, 1996)

Commentaires sur Ambient V, Secret de polichinelle et Danga - Sokolovic, Ana (Université de Montréal, 1996)

Violet Balestreri Archer: Milestones of a Career (Canadian University Music Review / Revue de musique des universités canadiennes, 1995)
Un article de la revue Canadian University Music Review / Revue de musique des universités canadiennes, diffusée par la plateforme Érudit.

Musica E Poesia Nell’ Opera di Violet Archer [Musique et poésie dans l'œuvre de Violet Archer] - Calo, Francesca (Université de Rome « La Sapienza », 1995)
Keywords: Pas de lien web

The Composer's Voice: "What women can do" - Dalen, Brenda (Canadian University Music Review / Revue de musique des universités canadiennes, 1995)
In this interview, conducted on 18 August 1994, Violet Balestreri Archer revisits her past, recreating the experiences of her youth from the earliest days of her childhood in Como and Montreal to her graduation from Yale University in 1949 and sharing highly personal memories of her family, teachers, and friends. She recalls her first visit to Italy, her school years, her piano lessons, her early attempts at composition, her participation in the Montreal Women's Symphony, and her compositional studies with Douglas Clarke at McGill University, Béla Bartók in New York, and Paul Hindemith at Yale University. In listening to her story, we discover "who" she is and "how" she succeeded in establishing her compositional voice and in creating a space or "room" for herself in a profession traditionally dominated by men.

The emergence of a new reality for Quebec Women Composers - Lefebvre, Marie-Thérèse (With a Song in Her Heart: A Celebration of Canadian Women Composers, 1995)

Creating Worlds For Music To Exist: How Women Composers of Electroacoustic Music Make Place For Their Voices - McCartney, Andra (Université York, 1995)

Whose Playground, Which Games and What Rules?: Women Composers in the Digital Playground - McCartney, Andra (International Composer Music Association, 1995)
Keywords: Pas de lien web

When Shirley Met Florence - Bezalel, Ronit (Office national du film du Canada, 1994)
Portrait intime de deux femmes juives au milieu de la soixantaine, l'une homosexuelle et l'autre hétérosexuelle, dont l'amour l'une pour l'autre et la musique qu'elles créent ensemble transcendent les différences. L'attachement de Florence pour Shirley défie toute catégorisation.

Existe-t-il une musique dite féministe ? - Lefebvre, Marie-Thérèse (Les Bâtisseuses de la Cité, 1993)

La musique composée au féminin - Martin-Kostajnsek, Sylvaine (Les Bâtisseuses de la Cité, 1993)

L'importance des femmes dans la vie musicale montréalaise entre les deux guerres: mythe ou réalité ? - Paul, Hélène (Les Bâtisseuses de la Cité, 1993)

Le couple Maubourg-Roberval : un apport décisif à l’implantation de l’art lyrique à Montréal - Paul, Hélène (L'Annuaire théâtral. Revue québécoise d’études théâtrales, 1993)
Un article de la revue L'Annuaire théâtral, diffusée par la plateforme Érudit.

Archives of Emma Albani - Willis, Stephen C. (National Library News, 1993)

Canada 125. Cantate profane pour chœur et orchestre, analyse musicologique - Badian, Maya (Lucian Badian Editions, 1992)

Die Komponistin Violet Archer unter Berücksichtigung ihrer nationalen und internationalen Stellung im Musikleben [La compositrice Violet Archer au regard de sa position nationale et internationale dans la vie musicale] - Glathe, Kerstin (Université de Münster, 1992)

The Creative Piano Constructions of Violet Archer - Parker, James Edward Kimura (Juilliard School, 1992)

Violet Archer: A Bio-Bibliography - Hartig, Linda (Greenwood Press, 1991)

La création musicale des femmes au Québec - Lefebvre, Marie-Thérèse (De mémoire de femmes, 1991)
Keywords: History and criticism; Music by women composers; Québec (Province); Women composers

Transit de Micheline Coulombe Saint-Marcoux : l’aboutissement du cheminement du créateur - Lévesque, Carole (Les Cahiers de l’ARMuQ, 1991)

Quel plain-chant pour la Nouvelle-France ? L'exemple des Ursulines - Pinson, Jean-Pierre (Canadian University Music Review, 1991)
S'il est une musique qui fut pratiquée en Nouvelle-France depuis les origines jusqu'au XXe siècle, ce fut bien celle du plain-chant1. Or, ce répertoire se présente comme un reflet souvent exact du plain-chant gallican, de son histoire et de sa pratique. Certes, il lui a fallu s'adapter aux lieux, aux populations et aux coutumes, mais sa répartition géographique, moins complexe qu'en France, et le nombre plus restreint d'institutions et de paroisses permettent une méthode d'approche à peu près contrôlable. Au cours de notre projet de recherche2, nous avons recueilli à travers le Québec des centaines de sources qui tracent un portrait riche de cette pratique. Mieux : au-delà du plain-chant lui-même c 'est en fait le chant baroque français qui s'est conservé longtemps ici, « sous cloche », dans un milieu très conservateur : ce chant de la Nouvelle-France est un beau cas de Performing practice. Parmi toutes les institutions visitées, les Ursulines de Québec et de Trois-Rivières3 constituent une excellente illustration de ce phénomène. Les sources conservées chez elles, classées dans l'annexe bibliographique, présentent une synthèse assez fidèle des sources demeurées en Nouvelle-France, contribuant ainsi à l'élaboration de ce portrait.

La formation professionnelle des filles dans les écoles supérieures de musique tenues par les religieuses, 1926-1960 - Mendez, Manon (Université de Sherbrooke, 1990)

Maureen Forrester. Au-delà du personnage. Un récit autobiographique - Forrester, Maureen; McDonald, Marci (Éditions Libre Expression, 1989)
Les petits et grands moments de la vie et de la carrière de l'artiste.

Les Ursulines et la musique - Gréroire-Reid, Claire; V. -Demers, Micheline (Cap-aux-Diamants : la revue d'histoire du Québec, 1989)

Analyse de la composition musicale Coulage - Pelletier, Marie (Université de Montréal, 1989)
Keywords: Pas de lien web

L’Abandon et Mosaïques : deux œuvres musicales, deux parcours - Carignan, Nicole (Université de Montréal, 1988)

Place aux femmes-compositeurs du Québec - Lefebvre, Marie-Thérèse (Les Cahiers de l'ARMuQ, 1988)

Pierrette Alarie et Léopold Simoneau. Deux voix, un art - Maheu, Renée (Éditions Libre Expression, 1988)

Emma Albani (1847-1930) - Potvin, Gilles (Les Cahiers de l'ARMuQ, 1988)

Notes on Violet Archer - Proctor, George A. (Musical Canada: Words and Music Honouring Helmut Kallmann, 1988)
Notes on Violet Archer was published in Musical Canada on page 188.

La création musicale chez les religieuses enseignantes de Montréal - Rhéaume, Claire (Cahiers de l'ARMuQ, 1988)

Éva Gauthier (1885-1958) : première cantatrice canadienne-française d’avant-garde - Turbide, Nadia (Les Cahiers de l'ARMuQ, 1988)

« Sursis», « Play room » [analyses] - Bertrand, Ginette (Université de Montréal, 1987)
Keywords: Pas de lien web

Les femmes compositeurs au Canada : données sociologiques et historiques - Kidd, Roseanne (Sonances, 1987)

L'implication sociale et créatrice de Micheline Coulombe Saint-Marcoux - Lévesque, Carole (Université McGill, 1987)

La création musicale chez les religieuses de trois communautés montréalaises - Rhéaume, Claire (Université de Montréal, 1987)

Out of Character - Forrester, Maureen; McDonald, Marci (McClelland & Stewart Publishing, 1986)

Biographical Study of Eva Gauthier (1885–1958): First French-Canadian Singer of the Avant-Garde - Turbide, Nadia (Université de Montréal, 1986)

Muséalogue : Maryvonne Kendergi - Bail Milot, Louise (Les Cahiers de l'ARMuQ, 1985)
Muséalogue : Maryvonne Kendergi

Au-delà du mur du son, l’univers consonant et dissonant d’Anne Lauber - Cloutier, Diane (La Scène musicale, 1984)

La musique de salon au Québec (1880-1915) - Geoffrion, Diane (Les Cahiers de l'ARMuQ, 1984)

Emma Albani: Victorian Diva - MacDonald, Cheryl (Dundurn Press, 1984)
Talented Emma Albani was a favourite of Queen Victoria, singing at Victoria's funeral as well as Edward VII's coronation, and for many other heads of state from Russia, Austria, France, Italy, Belgium, Denmark, United States and Canada. Sir Arthur Sullivan, Gounod, Von Flotow and Dvorak wrotemusic for her and she sang with Nellie Melba, Adelina Patti, Jean de Reszke, Francesco Tamagno among others. Emma, who married Ernest Gye, manager of Covent Garden, was celebrated as one of the leading operatic and oratorio sopranos of the century. Emma (Lajeunesse) Albani, one of Canada's first internationally known performers, began as a student singing in a Chambly, Quebec convent and an Albany, New York church. From her opera debut in April 1870 in Sicily to her farewell concert in October 1911 in London, England, she was loved for her voice as well as her kindness, which was rare in a prima donna. She was adored by fans world-wide as George Bernard Shaw recorded in 1889," ... people were standing two and three deep behind the chairs ..., consisting of prima donna worshippers who are bent on obtaining a bird's eye view of Madam Albani.

La musique de salon au Québec (1880-1915) - Geoffrion, Diane (Université de Montréal, 1983)

Éva Gauthier. De Java au Jazz - Turbide, Nadia (Aria, 1982)

The Motet in New France: Some 17 th and 18 th Century Manuscripts in Quebec - Schwandt, Erich (Fontes Artis Musicae, 1981)

The Choral Music of Violet Archer - Don Huiner, Harvey (Université d'Iowa, 1980)

Violet B. Archer : une élève canadienne de Bela Bartok - Lenoir, Yves (Institut supérieur d'archeologie et d'histoire de l'art, Université catholique de Louvain, 1980)

Une Canadienne à Moscou en 1873 - Potvin, Gilles (Bulletin du Centre de recherche en civilisation canadienne-française de l'Université d'Ottawa, 1979)

The Montreal Women's Symphony - Rooney, Frances (Atlantis, 1979)

Pauline Donalda: The Life and Career of a Canadian Prima Donna - Brotman, Ruth C. (Eagle Publishing, 1975)
Pauline Donalda (1882-1970) was born Pauline Lightstone in Montreal. She adopted the name "Donalda" after her benefactor, Donald Smith, Lord Strathcona. She studied music at Montreal's Royal Victoria College and in Paris, and made her opera debut in 1904 in Nice, France. In 1922 she opened a studio in Paris and became a teacher, and in 1937 she returned to Montreal where she opened a studio. In 1942 she founded the Opera Guild of Montreal. She served as President and Artistic Director of the Guild until 1969.

L'enseignement de la musique vocale et instrumentale aux Ursulines de Québec de 1830 à 1880 - Pagé, Thérèse (Université Laval, 1975)

Mémoires d’Emma Albani. L’éblouissante carrière de la plus grande cantatrice québécoise - Albani, Emma (Éditions du Jour,, 1972)

L'histoire de la musique de l'Institut des Sœurs de la Charité de Québec - Roy, Marielle (Université Laval, 1968)

Musiciennes de chez nous - Gingras, Claude (École de musique Vincent-d'Indy, 1955)

L’Albani. Sa carrière artistique et triomphale - Charbonneau, Hélène (Imprimerie Jacques-Cartier, 1938)

Albani (Emma Lajeunesse) - Legendre, Napoléon (Imprimerie A. Coté et Cie, 1874)
Le Rossignol du Canada français, la connaissiez-vous ? Auriez-vous aimer l'entendre chanter ? Une soprano tout en douceur... Voyez ce que le travail acharné a fait de cette dame une célébrité internationale.

Y a-t-il une compositrice en musique au programme ? - Carignan, Nicole; Vincent, Jean Windsow (Musique et pédagogie)